(untitled) (TAJ: Journal of Teachers Association, 2018)
To address the high infant and neonatal mortality rate in Bangladesh, government has adopted policy to ensure care for neonates from community to tertiary level of health care delivery system. Our country has achieved 4 MDG targets well before 2015. However the pace of reduction of neonatal mortality is much lower than that of older children. For that reason government of Bangladesh through Ministry of Health and Family Welfare established Special Care Neonatal Unit (SCNU) at secondary and tertiary level facilities to improve management of sick newborn. The aim of this study was to evaluate the impact of creating SCNU at district hospitals on newborn care practices and to evaluate the contribution of SCNU in improved neonatal survival. It was an observational study conducted from May 2016 to October 2016at 250-bed General Hospital, Sirajganj. Hospital database was accessed to note the number of neonatal admissions, number of referral to higher centers and neonatal mortality. A questionnaire was prepared to interview mothers of children admitted in SCNU and general pediatric ward. A total of 355 mothers were interviewed. There was a significant reduction in neonatal mortality rate after the establishment of SCNU. There was also significant improvement in the knowledge and awareness among mothers regarding various aspects of neonatal care because of the SCNU. TAJ 2017; 30(2): 65-68